Fine mapping a quantitative trait locus, qSER-7, that controls stigma exsertion rate in rice (Oryza sativa L.) - Yi Liu (Rice, 2019)
Abstract Background Stigma exsertion rate (SER) is a key determinant of outcrossing in hybrid rice seed production. A quantitative trait locus (QTL) for stigma exsertion rate in rice, qSER-7, has previously been detected on chromosome 7 by using a F2 population derived from two indica cytoplasmic male sterility (CMS) maintainers, Huhan 1B and II-32B. Results The chromosomal location of qSER-7 was precisely delimited by fine-scale mapping. Near-isogenic lines (NILs) were established, one of which isolated the locus in the qSER-7 II-32B line, which contains an introgressed segment of II-32B in the Huhan 1B genetic background, and exhibits a significantly higher stigma exsertion rate than that of the recurrent parent. Using 3192 individuals from the BC4F2 segregation population, the QTL qSER-7 was narrowed down to a 28.4-kb region between the markers RM3859 and Indel4373 on chromosome 7. According to the rice genome annotation database, three genes were predicted within the target region. Real-time PCR analysis showed significantly higher expression levels of LOC_Os07g15370 and LOC_Os07g15390 in II-32B than in Huhan 1B. LOC_Os07g15370(OsNRAMP5) was a previously reported gene for Mn and Cd transporter. The stigma exertion rates of OsNRAMP5-overexpressing plants were significantly higher than that of wild type plants, in contrast, a T-DNA insertion mutant osnramp5 showed a lower stigma exertion rate. Conclusions In the present study, the QTL qSER-7 was isolated to a region between the markers RM3859 and Indel4373. Two candidate genes were selected based on the expression difference between the two parents, which can facilitate the further cloning of the gene underlying the quantitative trait associated with qSER-7 as well as the marker-assisted transfer of desirable genes for stigma exsertion rate improvement in rice.